A cultural history of chess-players : minds, machines, and monsters - Sharples, John (Book collections on Project MUSE., 2017)
This inquiry concerns the cultural history of the chess-player. It takes as its premise the idea that the chess-player has become a fragmented collection of images, underpinned by challenges to, and confirmations of, chess's status as an intellectually-superior and socially-useful game, particularly since the medieval period.